K-AR GEOCHRONOLOGY OF NEW VOLCANIC CENTERS ERUPTIONS IN THE KAZBEK REGION OF THE GREAT CAUCASUS - Chernyshev I.V.; Arakelyants M.M.; Lebedev V.A.; Bubnov S.N.; Gol'tsman Yu.V. (My University, 1999)
The aim of this paper was to report and discuss the data available for the K-Ar dating of effusive rocks from a few centers of recent volcanic activity in the Kazbek region (Great Caucasus) of the Caucasian segment of the Mediterranean (or of the Alpine-Himalayan) mobile belt separating the African-Arabian and European platforms. These data were obtained using the special version of the K-Ar method, developed by the author, which allowed the reliable dating of the ultrayoung (Late Pleistocene) igneous rocks for the first time in Russia. We discovered and dated the period of the maximum igneous activity in the entire volcanic system of the Kazbek area (150-300 thousand years old) and verified the succession of the recent volcanic eruptions in this region. We proved that some of the volcanoes might have been active in Holocene time (younger than 10-15 thousand years). On this basis they can be ranked as potentially dangerous.
Keywords: GEOCHRONOLOGY OF NEW VOLCANIC CENTERS ERUPTIONS; KAZBEK REGION; MEDITERRANEAN MOBILE BELT